Situations Where It Is Appropriate to Use Frequency Estimation Equipercentile Equating. Issue 3 (23rd September 2013) - Guo, Hongwen; Oh, Hyeonjoo J.; Eignor, Daniel
<x xml:space="preserve">Abstract</x> In operational equating situations, frequency estimation equipercentile equating is considered only when the old and new groups have similar abilities. The frequency estimation assumptions are investigated in this study under various situations from both the levels of theoretical interest and practical use. It shows that frequency estimation equating can be used under circumstances when it is not normally used. To link theoretical results with practice, statistical methods are proposed for checking frequency estimation assumptions based on available data: observed‐score distributions and item difficulty distributions of the forms. In addition to the conventional use of frequency estimation equating when the group abilities are similar, three situations are identified when the group abilities are dissimilar: (a) when the two forms and the observed conditional score distributions are similar the two forms and the observed conditional score distributions are similar (in this situation, the frequency estimation equating assumptions are likely to hold, and frequency estimation equating is appropriate); (b) when forms are similar but the observed conditional score distributions are not (in this situation, frequency estimation equating is not appropriate); and (c) when forms are not similar but the observed conditional score distributions are (frequency estimation equating is not appropriate). Statistical analysis procedures for comparing distributions are provided. Data from a large‐scale test are used to illustrate the use of frequency estimation equating when the group difference in ability is large.